Cultivating spirituality in organizations: the role of spiritual discernment - Verdugo-Rojas, Carolina (Journal of management, spirituality & religion, 2025)
Organizational spirituality addresses the complexities of the organizational landscape. It requires the embodiment of spiritual practices within organizations. As one such spiritual practice, spiritual discernment is closely linked to decision-making, a critical aspect of organizational functioning. However, there is a need to establish a clear link between organizational spirituality and spiritual discernment, as this integration provides a way for organizations to begin their spiritual development. This paper presents a conceptual framework that identifies and clarifies the employee-enabling conditions—such as practical wisdom, appreciation of beauty and excellence, and social intelligence—and explains how these conditions facilitate the practice of spiritual discernment. This study advances the field of organizational spirituality by linking organizational spirituality with spiritual discernment, expanding the understanding of how spirituality can be systematically integrated into decision-making processes, and highlighting the role of employee capabilities in this integration.